2019
DOI: 10.18535/ijsrm/v7i7.el02
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation the Lesson Plan of English Language Learning in Junior High School, Seraphine Bakti Utama West Jakarta

Abstract: The study aims to evaluation the lesson plan of english language learning. This research was conducted at the Junior High School, Seraphine Bakti Utama West Jakarta. The research methodology used is evaluative through the flow of the gap model (discrepancy evaluation model). Data collection through interviews, document tracing, and observation. Key informant is the principal, teacher, and student. The results showed that: (1). The use of the lesson plan drafting principles occurs a negative (-) gap that reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Immediate feedback from online assessments allows teachers to spot misunderstandings that are not clear to students and resolve them before the final exam. The use of online assessments can reduce the burden on teachers to assess the large number of students (Evriana, 2020;Oktafianti, 2019;Mauliate et al, 2019). Google classroom should also be a form of student assessment through online assignments and quizzes to make students actively participate in educational technology classes.…”
Section: Resultsmentioning
confidence: 99%
“…Immediate feedback from online assessments allows teachers to spot misunderstandings that are not clear to students and resolve them before the final exam. The use of online assessments can reduce the burden on teachers to assess the large number of students (Evriana, 2020;Oktafianti, 2019;Mauliate et al, 2019). Google classroom should also be a form of student assessment through online assignments and quizzes to make students actively participate in educational technology classes.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, organizing the learning activities related to the learning process will be successful if students' needs are accommodated by the classroom activities facilitated by the teacher. In some previous studies, many teachers spent a lot of time planning activities in the classroom, which indicated that planning activities to be relevant with materials is not easy (Mauliate et al, 2019;Maulani, 2019;Sesiorina, 2014). In addition, the criteria of instructional activities; reflecting student-centered instruction, reflecting communicative method, motivate students to learn and expose foreign language, helping students to recall prerequisite, presenting information and examples, integrating the four skills (reading, listening, speaking, and reading), and providing practice and feedback.…”
Section: Discussionmentioning
confidence: 99%
“…The second difficulty found regarding the teacher's difficulties in designing lesson plans is in the steps of selecting the assessment types based on the learning objectives. Concerning this difficulty, the teacher mentioned this difficulty due to the difficulties in making the assessment, which is based on basic competencies and main competencies used in all topics of the lesson plan (Mauliate et al, 2019;Raynesa Noor Emiliasari, 2019). Based on those difficulties found, it can be synthesized that two difficulties occurred in designing the learning objectives, two difficulties in designing learning media and sources, one difficulty in learning materials, and another one were in the aspect of learning assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intended evaluation model is the Discrepancy-Tat Twam Asi model, which is integrated with the TOPSIS method calculations to obtain the dominant indicator determining blended learning effectiveness. The Discrepancy-Tat Twam Asi model is a combination of the educational evaluation model (Discrepancy) with one of the Balinese local wisdom concepts (Tat Twam Asi).The Discrepancy model is one of the evaluation models that provide recommendations based on gaps found from the evaluation results that are compared to established evaluation standards [8,9,10,11]. Tat Twam Asi is a concept of the Balinese people's local wisdom that shows the existence of tolerance, equal rights, or the same authority among human beings to create harmony [12,13,14].…”
Section: Introductionmentioning
confidence: 99%